2014
DOI: 10.1016/j.febslet.2014.05.014
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of multifunctional nucleolar protein nucleophosmin (NPM1) by aurora kinase B is critical for mitotic progression

Abstract: a b s t r a c tThe functional association of NPM1 with Aurora kinases is well documented. Surprisingly, although NPM1 is a well characterized phosphoprotein, it is unknown whether it is a substrate of Aurora kinases. We have found that Aurora kinases A and B can phosphorylate NPM1 at a single serine residue, Ser125, in vitro and in vivo. Phosphorylated-S125-NPM1 (pS125-NPM1) localizes to the midbody region during late cytokinesis where it colocalizes with Aurora B. The overexpression of mutant (S125A) NPM1 res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 25 publications
1
10
0
Order By: Relevance
“…CK2 is thought to maintain the basal phosphorylated state of PC4 during interphase, but the kinase responsible for PC4 phosphoenrichment (hyperphosphorylation) during mitosis was not known. A similar situation was observed with NPM1 until it was found to be a target of Aurora kinase A and B during the cell cycle [16,18]. Our studies revealed that the phosphorylation of PC4 by Aurora kinase had important functional consequences for mitosis.…”
Section: Discussionsupporting
confidence: 83%
“…CK2 is thought to maintain the basal phosphorylated state of PC4 during interphase, but the kinase responsible for PC4 phosphoenrichment (hyperphosphorylation) during mitosis was not known. A similar situation was observed with NPM1 until it was found to be a target of Aurora kinase A and B during the cell cycle [16,18]. Our studies revealed that the phosphorylation of PC4 by Aurora kinase had important functional consequences for mitosis.…”
Section: Discussionsupporting
confidence: 83%
“…Notably, CIGB-300 has been subjected to several phase I clinical trials and has entered phase II [151,152]. Interestingly, CIGB-300 was shown to bind NPM1 and to inhibit CK2-mediated phosphorylation of NPM1 at Ser125 inducing damage to the nucleolar architecture and massive apoptosis [149], in line with the putative implication of NPM1 phospho-Ser125 in the maintenance of the nucleolar assembly, in ribosome biogenesis, and in cytokinesis [153][154][155].…”
Section: Synthetic Compoundsmentioning
confidence: 90%
“…The NPM1 protein is a nuclear chaperone that can be converted in the nucleus and cytoplasm, and has various types of biological functions, including gene stability, DNA repairs, tumorigenesis, etc. . Studies have shown that NPM1 protein can regulate the localization, aggregation and stability of P53 and p14 ARF proteins, thereby playing an important role in tumorigenesis .…”
Section: Discussionmentioning
confidence: 99%